IPAL EFEKTIVITAS BIOFILTER DALAM MEREDUKSI POLUTAN PADA AIR LIMBAH RUMAH SAKIT DI KOTA PALU - Pitriani Pitriani; Mutmainnah Maulani; Trivena Tatulus; Farida Indriani; Kiki Sanjaya; Nurdin; Lusia Salmawati (Universitas Wiralodra, 2022)
The existence of pollutants in hospital wastewater has the potential to pollute the environment, so they are obliged to process the liquid waste before it is released into nature. To ensure that wastewater is feasible to be discharged into the environment, it is necessary to treat it through a Wastewater Treatment Plant, one of which is the aerobic anaerobic biofilter method. This study aims to determine the effectiveness of anaerobic aerobic biofilter in reducing pollutants in wastewater in terms of the physical, chemical and biological parameters. This study uses a quasi experiment with sampling technique composite sample by time. Color and odor parameters were checked organoleptically, while pH and temperature were measured insitu using a multifunctional portable device. Parameters of BOD, COD, NH3, TSS and MPN Coliform analyzed in the laboratory for quality assurance of each sample is checked duplo. The study results of the Anutapura Hospital's wastewater treatment are still a slighly cloudy but odorless, this is not in accordance with the wastewater quality standards in the Minister of Environment Regulation Number 5 of 2014, on the contrary at Madani Hospital the color and odor parameters have met the quality standards. The values of temperature, pH, BOD, COD and TSS have met the quality standard requirements at both hospitals even from the inlet point. this is because it is good of preliminary treatment to be carried out before the wastewater flows into the biofilter. While the value of TSS and MPN coliform, at the inlet and outlet point has exceeded the quality standard. The effectiveness percentage of BOD reduction in Anutapura Hospital and Madani Hospital is 70.2% and 47.6%, for COD reduction is 53.4% and 27%, NH3 reduction 95.9% and 69.4% and TSS reduction is 65.2% and 70.2%. Based the data, concluded that increasing the percentage of biofilter effectiveness is still necessary. Keywords: anaerobic, aerobic, biofilter, WWTP